Eudragit-Coated Sporopollenin Exine Microcapsules (SEMC) of Phoenix dactylifera L. of 5-Fluorouracil for Colon-Specific Drug Delivery - Mohammad Raish; Mohd Abul Kalam; Ajaz Ahmad; Mudassar Shahid; Mushtaq Ahmad Ansari; Abdul Ahad; Raisuddin Ali; Yousef A. Bin Jardan; Aws Alshamsan; Musaed Alkholief; Khalid M. Alkharfy; Ibrahim Abdelsalam Abdelrahman; et al. (MDPI AG, 2021)
In this study, 5-fluorouracil (5-FU)-loaded pollens of Phoenix dactylifera and their coating with ERS was done and evaluated for the colon-targeted delivery of 5-FU to treat colon cancer. Sporopollenin exine microcapsules (SEMC) from the pollens of Phoenix dactylifera were extracted by the reflux method and 5-FU into SEMC was encapsulated by the vacuum-assisted loading method. 5-FU loaded SEMC was coated with Eudragit® RS-100 (ERS) by the organic solvent-evaporation technique under vacuum to avoid the discharge of 5-FU in the stomach and small intestine. Morphological and physicochemical characterization of drug-loaded SEMC (coated/uncoated) was performed by scanning electron microscopy (SEM), FTIR, XRD, and DSC. The encapsulation and drug loading were determined by the direct method, and an in vitro release study was performed in simulated gastric and intestinal fluids (SGF/SIF). The colon-specific delivery of 5-FU from the SEMC was assessed in terms of pharmacokinetics and gastrointestinal tract distribution after oral administration in rats. The successful encapsulation and loading of 5-FU into SEMC by a vacuum-assisted loading technique and its coating with ERS by a solvent-evaporation technique were achieved. SEM images of uncoated SEMC have shown porous structures, and coating with ERS reserved their morphology with a smooth surface and discrete microstructures and the 5% w/v ERS acetone solution. ERS-coated SEMC sustained the release of 5-FU until 24 h in SIF, while it was up to 12 h only from uncoated SEMC. The maximum plasma concentration (Cmax) of 5-FU from uncoated SEMC was 102.82 μg/mL after 1 h, indicating a rapid release of 5-FU in the upper gastrointestinal tract. This concentration decreased quickly with a half-life of 4 h, AUC0-t was 264.1 μg/mL.h, and MRT0-inf was 5.2 h. The Cmax of 5-FU from ERS-coated SEMC was 19.47 μg/mL at 16 h. The Cmax of 5-FU in small intestines was 406.2 μg/g at 1 h from uncoated SEMC and 1271.5 μg/g at 12 h from coated SEMC. Conclusively, a 249.9-fold higher relative bioavailability of 5-FU was achieved with the ERS-coated SEMC in colon tissues than that from uncoated SEMC.